People living with HIV and AIDS in everyday conditions of township life in South Africa: between structural constraint and individual tactics - Frédéric Le Marcis; Rehana Ebrahim-Vally (Taylor & Francis Group, 2005)
The HIV/AIDS pandemic in South Africa has negatively transformed the lives of many in townships and rural areas. People living with AIDS (PWAs) are the socially weakened, whose means of survival include migrating, enduring gender violence, and they are thus confined to living in the margins of society. Using the concept of tactic as defined by de Certeau, this paper shows how anthropology can use the narratives of everyday life to make sense of the different ways the socially weakened create networks of support, find a cure, and generate forms of income or use running away as a means to avoid gender violence. This paper argues that if the State hopes to successfully introduce antiretroviral therapy and so turn everyday logics of survival into long-term strategies, it needs to commit itself firmly to reducing inherited forms of inequalities. Similarly, the State's commitment to eradicate poverty also requires it to take cognisance of the different borderline activities the socially weakened regard as avenues of survival. Rather than morally condemn such activity as a wrongdoing, the State should enhance its knowledge of the socio-economic conditions that almost coerce the socially weakened to 'do wrong'. The data were collected during intensive fieldworlk carried out in Alexandra township and Diepkloof (Gauteng) in 2001 - 2002, using participant observation and repeated in-depth interviews.